2021
DOI: 10.2196/21461
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Technology Preferences and Requirements for Health Information Technologies Designed to Improve and Maintain the Mental Health and Well-Being of Older Adults: Participatory Design Study

Abstract: Background Worldwide, the population is aging rapidly; therefore, there is a growing interest in strategies to support and maintain health and well-being in later life. Although familiarity with technology and digital literacy are increasing among this group, some older adults still lack confidence in their ability to use web-based technologies. In addition, age-related changes in cognition, vision, hearing, and perception may be barriers to adoption and highlight the need for digital tools develop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 44 publications
(53 reference statements)
3
41
0
1
Order By: Relevance
“…Additionally, the systematisation of the assessment and monitoring process ensures transparency of outcomes for both consumers and health professionals, which is particularly relevant as health professionals tend to overestimate the benefits of care relative to measured outcomes [36]. Importantly, our own research has shown that the ability to track data over time is valued by consumers as a means to better understand what information, resources and intervention strategies are associated with positive health outcomes [37]. Furthermore, symptom tracking and real-time feedback improves engagement and promotes behaviour change [38].…”
Section: Technology-enabled Enhancements In Care Based On Key Performmentioning
confidence: 99%
“…Additionally, the systematisation of the assessment and monitoring process ensures transparency of outcomes for both consumers and health professionals, which is particularly relevant as health professionals tend to overestimate the benefits of care relative to measured outcomes [36]. Importantly, our own research has shown that the ability to track data over time is valued by consumers as a means to better understand what information, resources and intervention strategies are associated with positive health outcomes [37]. Furthermore, symptom tracking and real-time feedback improves engagement and promotes behaviour change [38].…”
Section: Technology-enabled Enhancements In Care Based On Key Performmentioning
confidence: 99%
“…As the global population rapidly ages, there has been an increased focus on the development of strategies to support and maintain health and well-being in later life. As described in detail in our previous work [1], the international literature indicates that approximately two-thirds of adults aged ≥65 years report internet use [2,3], and these older adults also represent the fastest growing group of internet users [4]. Globally, government initiatives have been launched to improve the digital literacy and web-based safety of older adults [5,6].…”
Section: Capitalizing On Technology To Support Health and Well-beingmentioning
confidence: 99%
“…Through participatory design, we configured a prototype of the InnoWell Platform specifically for older adults, including modification of health domains, informational material, and care options, to ensure relevance and appropriateness for this end user group [1]. This study, a supplement to the original co-design research, aims to evaluate the usability and acceptability of the prototyped older adult configuration of the InnoWell Platform.…”
Section: The Innowell Platformmentioning
confidence: 99%
See 2 more Smart Citations